A FIT BETWEEN INDIVIDUAL AND ORGANIZATIONAL VALUES AND ITS IMPLICATIONS FOR EMPLOYEES’ JOB SATISFACTION AND PERFORMANCE - Diskienė, Danuta; Goštautas, Vytautas (Ekonomika, 2013)
Abstract. The importance of studies on work-related values and attitudes is obvious as values are ascribed a central role in determining the fit between individuals and the employment organization. Responding to the importance of the issue, the paper emphasizes the meaning of the individual and organizational values’ fit for the organization, its possibility to become part of strategic planning and a goal for every manager in charge. The aim of the article is to explore the theoretical concepts on values’ fit and to compare it with the empirical research findings. The research question is how the individual and organizational values’ fit is related with the job satisfaction and performance of the employees. Adapted methods of the survey of job satisfaction measuringnine different facet scales, were used, performance results were obtained from the organization, and two different variables related to quality and sales were measured. The research was conducted in the Lithuanian Telecommunication company. The findings of the research emphasize that job satisfaction has significant correlations with individual and organizational values’ fit. Employees whose job satisfaction was higher had higher fit scores. The performance of employees had no significant correlation with job satisfaction scales.Key words: individual values, organizational values, values fit, job satisfaction, performance